The influence of Indonesia’s macroeconomic factors: Inflation and interest rate on large-cap cryptocurrency herding behavior - Muhamad Rizky Ramadhan; Wita Juwita Ermawati; Anna Fariyanti (Journal of Accounting and Investment, 2023)
Research aims: This study aims to investigate herding behavior in the large-capitalization cryptocurrency market and analyze the role/influence of Indonesia's macroeconomic factors, namely inflation and interest rates, on herding behavior in the large-cap cryptocurrency market.Design/Methodology/Approach: This study used secondary data from the daily closing prices of five large-cap cryptocurrencies and Indonesia's macroeconomic data (inflation and interest rates) from April 2019 to December 2022 by using the Cross-Sectional Absolute Deviation (CSAD) model and Newey-West estimator regression approach to detect herding behavior with a modified independent variable model involving factors influencing herding behavior.Research findings: Based on the results using the Newey-West estimator, three main results were obtained. First, large-cap cryptocurrency investors tend to be irrational in their decisions and follow the decisions of others without reference to their beliefs or herding during the sample period. Second of the two macroeconomic factors studied, i.e., inflation and interest rates, only changes in inflation rates influence investor herding behavior. Third, the market is inefficient with the proven tendency of herding behavior in large-cap cryptocurrencies.Practical and Theoretical contribution/Originality: This study narrows down the research of previous studies by using cryptocurrency research objects with a large market capitalization (large cap). In addition, this research extends the research of previous studies by considering external factors related to macroeconomic conditions in Indonesia in general, such as the inflation rate and the interest rate. This study can provide information about financial behavior in the cryptocurrency market, especially herding behavior, so that investors and policymakers can be assisted in formulating investment strategies and regulating cryptocurrencies.Research limitation: This research was limited to using only cryptocurrency assets by not using crypto-tokens, non-fungible tokens (NFT), and other crypto-assets.